UPLC METHOD DEVELOPMENT AND VALIDATION FOR THE ESTIMATION OF RISEDRONATE IN FORMULATION - ReddyN, Nagi; RaoJ, Venkateshwar (Asian Journal of Pharmaceutical and Clinical Research, 2013)
Rapid and sensitive Ultra performance liquid chromatography method was developed and validated for quantification of Risedronate in pharmaceutical formulation. The analysis is resolved by using symmetry C18, (100 × 2.1 mm), 1.7µm column; make BEH, in an Isocratic mode, with mobile phase containing Methanol and Water in the ratio of 70:30 v/v was used. The flow rate was 0.8 ml/min and the analyte was monitored at 273 nm by UV detection. The retention time for Risedronate sodium was 2.29 mints. The method was validated for system suitability, linearity (correlation coefficient 0.999), precision, accuracy (recovery studies 98percent-102percent), specificity, ruggedness, robustness, LOD (2.98µg/ml) and LOQ (9.94µg/ml). This present method is simple, highly sensitive, precise and accurate and has the potential of being useful for routine quality control. Key Words: Risedronate; UPLC; Validation